I worked my way through this problem and ended up with 0 = 1/2.... which is not correct. =P
The problem is:
y y' = (e^2 - 1 + y^2) xe^x^2
And the condition is y(0) = 1.
I know you have to change y' to dy/dx, and then get all the y's on one side and all the x's on the other, so I got:
(ydy) / (e^2 - 1 + y^2) = xe^x^2 dx
I'm thinking I went wrong when I tried to integrate it, specifically on the left-hand side.
xe^x^2 integrated is (e^x^2) / 2, right?
And on the left, I got (y^2 / 2)(x / e^2 - 1 + y^2), which is where I have a feeling I went wrong.
Any help is appreciated, thanks!
2007-03-19
16:33:25
·
2 answers
·
asked by
Sam D
1
in
Science & Mathematics
➔ Mathematics